Suppression of gene amplification and chromosomal DNA integration by the DNA mismatch repair system - Lin, Ching-Tai (Oxford University Press, 2001)
Mismatch repair (MMR)-deficient cells are shown to produce >15-fold more methotrexate-resistant colonies than MMR normal cells. The increased resistance to methotrexate is primarily due to gene amplification since all the resistant clones contain double-minute chromosomes and increased copy numbers of the DHFR gene. In addition, integration of linearized or retroviral DNAs into chromosomes is also significantly elevated in MMR-deficient cells. These results suggest that in addition to microsatellite instability and homeologous recombination, MMR is also involved in suppression of other genome instabilities such as gene amplification and chromosomal DNA integration.